2011
DOI: 10.1007/s12665-011-1379-z
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of total and methylmercury concentrations in soils near the Idrija mercury mine, Slovenia, and the dependence of the mercury concentrations on the chemical composition and organic carbon levels of the soil

Abstract: Although the mining activity of the Idrija mine in Slovenia ceased in 1995, a large amount of mining dregs containing high concentrations of mercury remains in the area. The mining dregs were transported with river flow and deposition along the Idrija River. To estimate the dispersion and change in the chemical form of mercury, a total of 28 soil core samples were taken around the river. The individual core samples were separated into layers for the analysis of their chemical composition, carbon contents, tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Soil samples collected in this study show a correlation between methyl-Hg and TOC ( r 2 = 0.57, p < 0.001; Fig. 4 ), which is consistent with the affinity of methyl-Hg for organic matter and similar to results found in other studies of Hg mined areas (Rimondi et al 2012 ; Tomiyasu et al 2012 ). The methyl-Hg data for soil indicate generally low conversion of inorganic Hg (dominantly HgS) to the highly toxic methyl-Hg.…”
Section: Resultssupporting
confidence: 91%
“…Soil samples collected in this study show a correlation between methyl-Hg and TOC ( r 2 = 0.57, p < 0.001; Fig. 4 ), which is consistent with the affinity of methyl-Hg for organic matter and similar to results found in other studies of Hg mined areas (Rimondi et al 2012 ; Tomiyasu et al 2012 ). The methyl-Hg data for soil indicate generally low conversion of inorganic Hg (dominantly HgS) to the highly toxic methyl-Hg.…”
Section: Resultssupporting
confidence: 91%
“…We distribute releases associated with mining activities along the locations of Hg mines obtained from mineral resources data system (MRDS) [ 35 ] and gold deposits [ 36 ], similar to the approach used by Selin et al [ 37 ] for distribution of geogenic Hg emissions. A 10 km buffer zone surrounding Hg and Au mines was used to delineate the contributing area, based on reported extent of pollution in various studies [ 38 , 39 , 40 , 41 ]. Different ranges of Hg releases were then considered depending on the climatic position of the site: 10–100, 100–1000 and 1000–3000 g·Hg·km −2 ·a −1 in case of primary Hg mining [ 41 , 42 ] for arid, temperate and humid climate zone [ 30 ], respectively, while order of magnitude lower loads were considered for Au mining sites.…”
Section: Methodsmentioning
confidence: 99%
“…The same behavior has been recently found in soils near an old mercury mine. 76 However, the strongest correlation was found between organic Hg and Hg concentrations in fraction F3. It has been suggested that elemental Hg present in mine sites, through time, can be converted to Hg(II) compounds, mostly by oxidation, and further methylated by methylating bacteria.…”
Section: Mobility and Availability Of Hgmentioning
confidence: 91%